A Guide to Conducting Systematic Reviews of Coaching Science Research - Bennie, A.; Apoifis, N.; Caron, J.; Falcão, W.; Marlin, D.; Garcia Bengoechea, E.; Teck Koh, K.; Macmillan, F.; George, E. (International Sport Coaching Journal, 2017)
Research in coaching science continues to grow and as such, there is a need for rigorous tools to help make sense of the rapidly expanding literature. The purpose of this paper is to provide a detailed description of a systematic review methodology that can be used to summarise literature in coaching science. To do so, we present a test case of a systematic review we conducted on the sport coaching experiences of global Indigenous populations. More precisely, we conducted a systematic review of English, Spanish, French, Mandarin, and Portuguese peer-reviewed journal articles, spanning twelve databases (e.g., Sport Discus, ERIC, and Scopus) from 1970 to 2014. ENTREQ and COREQ guidelines were followed to report the results of the systematic review, and Bronfenbrenner`s ecological systems theory was used as a theoretical framework to extract and synthesise relevant findings from the included articles. In sum, this paper presents a robust methodology for systematically reviewing research in coaching science and provides practical insights for those who endeavour to conduct rigorous literature searches in this domain.